Предмет: Алгебра,
автор: elena1314
упростите выражение
(x-4)(x-5)-2x(x-6)
7y(x+y-p)-7p(x-y-p)+7y(x-y+p)
Ответы
Автор ответа:
0
(х-4)(х-5)-2х(х-6)=
=х^2-5х-4х+20-2х^2+12х=
=-х^2+3х+20
7у(х+у-р)-7р(х-у-р)+7у(х+у+р)=
=7ху+7у^2-7ур-7хр+7ур+7р^2+7ху+7у^2+7ур=
=14ху+14у^2-7хр+7ур+7р^2
^2 - в квадрате
=х^2-5х-4х+20-2х^2+12х=
=-х^2+3х+20
7у(х+у-р)-7р(х-у-р)+7у(х+у+р)=
=7ху+7у^2-7ур-7хр+7ур+7р^2+7ху+7у^2+7ур=
=14ху+14у^2-7хр+7ур+7р^2
^2 - в квадрате
Автор ответа:
0
-0,5у(4-2у^2)(у^2+3)=-0,5у(4у^2+12-2у^4-6у^2)=
Автор ответа:
0
-0,5у(4-2у^2)(у^2+3)=-0,5у(4у^2+12-2у^4-6у^2)=-2у^3-6у+у^5+3у^3=у^5+у^3-6у
Похожие вопросы
Предмет: Физкультура и спорт,
автор: abramovavladislava52
Предмет: Математика,
автор: Missnam83
Предмет: Английский язык,
автор: fedya00pedya
Предмет: Химия,
автор: Илья200001